Peran Magang di Dinas Pemuda dan Olahraga Kota Medan dalam Mengembangkan Kemampuan Komunikasi Publik Mahasiswa Ilmu Komunikasi UINSU - Hasan Sazali; Afifah Rahmania; Alsha Nazwa; Annisa Rosa Mora Harahap; Haryati Haryati; M Nur Badawani Siregar (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
An internship is a learning program in the world of work that allows students to gain direct experience in a company or agency. This research aims to determine the role of internships at the Youth and Sports Department in developing public communication skills for Communication Science students. This research uses a qualitative approach with a case study method using Symbolic Interactional Theory. The research informants consisted of Communication Science students who were doing internships at the Youth and Sports Department as well as several supervisors at the agency. Data was collected through interviews, documentation and observation. The research results show that internships at the Youth and Sports Department provide significant development of public communication skills through tasks such as social media management, information center sections, correspondence, as well as planning and implementing public events. Apart from that, students also gain experience communicating with various parties. This research concludes that the internship program at the Youth and Sports Department plays an important role in improving the public communication skills of Communication Science students.